Challenges to professional football companies and their answers with particular regard to organisational changes - Bába Éva Bács (DANUBE: Law, Economics and Social Issues Review, 2014)
Professional football has been going through a period of unprecedented economic growth since the '90s. Football ventures are increasingly becoming medium-sized companies. There have also been organizational changes, reflected in changes in the legal forms of professional football clubs, and in the use of modern controlling, planning, risk and financial management. Important questions remain unanswered with regard to the financing of football clubs, such as the impact of risks or the market value of capital costs. In addition to liquidity and the above, the acceptance of the determinational dependence of certain capital funds on sports results and the development of a strategy suitable for the optimal target system are also important requirements. In this article, we would like to present the answers football companies have given to the challenges they have been facing which affect their organisational system. In the light of international comparison, we examine the status of Hungarian football, which was once world famous and enjoyed better times in the past.
Keywords: 330; Professional Football; Legal Forms; Organizational Structure; Controlling; Controlling System Building in Football Undertakings